PENERAPAN MODEL PEMBELAJARAN PjBL BERBASIS PODCAST UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK DALAM PEMBELAJARAN SEJARAH KELAS X SMAN 19 PEKANBARU - Annisa Lubis, Dhea; Bunari, Bunari; Asril, Asril (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low critical thinking skills of students in history learning, as evidenced by students' difficulties in analyzing events, evaluating information, and drawing logical conclusions. Based on these issues, this study aims to examine teacher activities, student activities, and the improvement of students' critical thinking skills through the implementation of a Podcast-based Project Based Learning (PjBL) model in history learning for grade X at SMAN 19 Pekanbaru. The research method used is classroom action research (CAR) conducted in two cycles. Each cycle consists of the stages of planning, implementation, observation, and reflection. The research subjects were grade X-1 students totaling 32 people, with data collection techniques through observation and documentation. The research results show that the implementation of the podcast-based PjBL model is able to improve students' critical thinking skills. The results from cycle I obtained a percentage of 39.84% with a 'low' category and increased in cycle II, which reached a percentage of 73.83% with a 'Good' category. The results in cycle II have already reached the percentage of achievement indicators, namely ≥70%. In addition, the activities of teachers and students also showed improvement, marked by more active student involvement in discussions, planning, and podcast project presentations. Thus, the podcast-based PjBL model has been proven effective in enhancing students' critical thinking skills in history learning.